1976
DOI: 10.1111/j.1600-0560.1976.tb00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Generalized Dyschromic Amyloidosis Cutis

Abstract: A generalized form of primary cutaneous amyloidosis was found in two siblings when microscopic examination was carried out on areas of scattered hypopigmentation. Multiple biopsies from different sites of the skin suggested that the pigmentary disorder was probably a process independent of the amyloidosis. One of the siblings died of interstitial pulmonary fibrosis, congenital pulmonary stenosis and diabetes mellitus. Post mortem examination of the lungs showed the presence of few amyloid deposits in the diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…[80] This rare entity was first described by Eng et al . [87] and thereafter several familial clusters have been described by others. [8889]…”
Section: Reticulate Lesions In Metabolic Disordersmentioning
confidence: 98%
“…[80] This rare entity was first described by Eng et al . [87] and thereafter several familial clusters have been described by others. [8889]…”
Section: Reticulate Lesions In Metabolic Disordersmentioning
confidence: 98%
“…235 It is suggested that this latter form might be related to amyloidosis cutis dyschromic, which is another familial type of amyloidosis characterized by reticulate hyperpigmentation and hypopigmentation of the trunk and limbs. [236][237][238] CONCLUSIONS Amyloidosis is a disease due to the deposit of amyloid, a complex substance mainly (but not only) made of proteins. The latter can be immunostained in many cases in the biopsies of the involved organs, so a closely approached diagnosis can be obtained.…”
Section: Some Variations In Plcamentioning
confidence: 98%
“…Therefore, we suggest a broad term, 'poikiloderma-like cutaneous amyloidosis syndrome (PCA syndrome)' for this [4] reported two siblings having suffered from an extensive discoloration with cutaneous amyloid deposits since childhood. This generalized form of primary cutaneous amyloidosis may be similar to the PCA syndrome, but there is not description of other complications involved in the syndrome.…”
Section: Commentmentioning
confidence: 99%